2009
DOI: 10.1016/j.ijrobp.2008.10.042
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Failure After Reirradiation of Recurrent Squamous Cell Head and Neck Cancer: Implications for Defining the Targets

Abstract: Purpose Re-irradiation (re-RT) of recurrent head and neck cancer (HNC) may achieve long term disease control in some patients, at the expense of high rates of late sequelae. Limiting the re-RT targets to the recurrent gross tumor volume (rGTV) would reduce the volumes of re-irradiated tissues, however, its effect on tumor recurrence pattern is unknown. Methods Retrospective review of 66 patients who underwent curative-intent re-RT for non-resectable recurrent or second primary mucosal squamous cell HNC. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 28 publications
(34 reference statements)
2
76
1
2
Order By: Relevance
“…Our fourth consideration was the use of sensitizing concurrent chemotherapy, used in 86%, which may have also contributed to the toxicity profile. As a fifth consideration, we kept the target volume at the minimum necessary, as established in head and neck reirradiation [19]. Advanced imaging (PET/CT) was utilized in this study to help distinguish tumor or tumor bed from surrounding inflammation or edema.…”
Section: Discussionmentioning
confidence: 99%
“…Our fourth consideration was the use of sensitizing concurrent chemotherapy, used in 86%, which may have also contributed to the toxicity profile. As a fifth consideration, we kept the target volume at the minimum necessary, as established in head and neck reirradiation [19]. Advanced imaging (PET/CT) was utilized in this study to help distinguish tumor or tumor bed from surrounding inflammation or edema.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the published literature on reirradiation using IMRT are rare [3,6,21]. Recently Sulman et al [30] reported 54 patients with definitive IMRT reirradiation (median dose, 66 Gy) and concurrent platinum-based chemotherapy resulting in a median OS of 25 months and a 2-year LCR of 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Previously irradiated tissue tends to be more hypoxic and therefore frequently more radioresistant. Popovtzer et al reported 92% of the third recurrence was the in-field of the second irradiation (reirradiation), which occurred in 77% of median 68-Gy-reirradiated patients in 154 relapsed squamous head and neck cancer patients [Popovtzer, 2009]. This suggests much higher dose may be biologically required to overcome the reparability of recurrent tumor after initial radiotherapy.…”
Section: Hypoxic Environment Of Reirradiation Targetmentioning
confidence: 99%